2013
DOI: 10.1016/j.pedneo.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the First Human Milk Bank in Taiwan

Abstract: Proper management and operation of a human milk bank can support breastfeeding, and provide a safe alternative to artificial formula for feeding preterm or ill infants in Taiwan. Sustainability of the milk bank needs more propagation and financial support by health authorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 11 publications
5
46
0
4
Order By: Relevance
“…Milk donors were unpaid volunteers, most of whom delivered term infants (91.2%). Most of the donor milk was mature milk because 96.5% of mothers donated their human milk at >1 month postpartum [18]. The protocol of this study was approved by the Institutional Review Board of Taichung Veterans General Hospital, and informed consent was obtained from all mothers.…”
Section: Methodsmentioning
confidence: 99%
“…Milk donors were unpaid volunteers, most of whom delivered term infants (91.2%). Most of the donor milk was mature milk because 96.5% of mothers donated their human milk at >1 month postpartum [18]. The protocol of this study was approved by the Institutional Review Board of Taichung Veterans General Hospital, and informed consent was obtained from all mothers.…”
Section: Methodsmentioning
confidence: 99%
“…In the meta-analytic study carried out by Quigley et al [22], it was determined that donor breast milk decreases necrotizing enterocolitis incidence in preterm infants. Different studies have also [23][24][25] reported that premature and low birth-weight infants who are breastfed milk taken from breast milk banks have their immune system boosted and thus are protected from many illnesses.…”
Section: Studies On Wet Nursing and Breast Milk Banksmentioning
confidence: 99%
“…In a study made in Turkey [32], it was determined that health personnel have a positive opinion regarding breast milk banks but their level of knowledge is low. The studies made [24,33] suggests important responsibilities fall to health personnel in order for breast milk banks to be adopted by the society.…”
Section: Studies On Wet Nursing and Breast Milk Banksmentioning
confidence: 99%
“…), DSÖ ve UNICEF (2009) bebeğin kendi annesinden anne sütü verilmesine en iyi alternatifin, sağlıklı bir sütanneden ya da bir anne sütü bankasından sağlanması gerektiğini bildirmektedir. 4,5 Amerikan Pediatrist Akademisi (AAP) ise; "bütün preterm bebeklerin anne sütü alması gerektiğini, önemli derecede laktasyon desteğine rağmen emzirme veya annenin kendi sütü uygun değilse, pastörize edilmiş bağışçı sütünün kullanılması gerektiğini" belirtmektedir. 6 Geç başlangıçlı sepsis ve nekrotizanenterokolit (NEC), yüksek morbidite ve mortalite riski taşıyan prematüre ve hasta bebeklerde iki önemli komplikasyondur.…”
Section: Anne Sütü Ve Bağışçı (Donör) Sütüunclassified